Ethnobotanical study on traditional cosmetics practiced by the Dayak Kayong of West Kalimantan, Indonesia - LEONI CLARA SELVITA SARI; IRWAN LOVADI; ELVI RUSMIYANTO PANCANING WARDOYO; AGUSTI RANDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sari LCS, Lovadi I, Wardoyo ERP, Randi A. 2024. Ethnobotanical study on traditional cosmetics practiced by the Dayak Kayong of West Kalimantan, Indonesia. Biodiversitas 25: 2937-2944. Various ethnic groups across the globe have practiced traditional cosmetics and many studies on cosmetic plants and their uses in Indonesia have been conducted. However, there is no ethnobotanical information on cosmetic plants and their uses, particularly in Dayak Kayong of Ketapang District, West Kalimantan, Indonesia. This study reports on cosmetic plants and their traditional uses by the Dayak Kayong community. We conducted semi-structured interviews from April to June 2022 with 30 respondents living in Nanga Tayap Sub-district in Ketapang District. Non-probability sampling was employed to select respondents based on their knowledge and practice of traditional cosmetics. Three indices, namely Frequency of Citation (FC), Informant Consensus Factor (ICF), and Fidelity Level (FL), were employed to analyze the ethnobotanical data. The Dayak Kayong community utilizes 26 plant species from 20 families for traditional cosmetics. The most frequently used plant part are leaves (34.62%), followed by fruits (19.23%), sap (15.38%), rhizomes (11.54%), flowers (11.5%), roots (3.85%), and seeds (3.85%). Important cosmetic plants based on FL include Aquilaria malaccensis, Areca catechu, Dendrobium sp., Gluta renghas, Lansium domesticum, and Sindora sp. The high FL documented for cosmetic plants in this study needs further investigation into potential plants for use in the cosmetics industry.